The Stratta Strategy for Creative Drama Learning in the Corona Virus Pandemic - Nurhasanah, Een; Maspuroh, Uah (Universitas Pahlawan Tuanku Tambusai, 2021)
A significant component of literary works, drama is one of the elements that must be taught in college, particularly in study programs focusing on language and literature education. The findings of this study describe the results of the learning process for Indonesian Drama Appreciation courses that were conducted using the Stratta learning strategy. As defined by the realms of learning Waluyo theory, there are three stages in this strategy for teaching literature. These stages are as follows: the exploration stage, which encompasses the cognitive realm; the interpretation stage, which includes the affective domain; and the recreational stage, which consists of the psychomotor realm. The qualitative descriptive method was employed in this investigation. Students enrolled in Indonesian drama appreciation courses in semester IV, five classes, were asked to research the subject. The collection of research data is a learning process. The findings revealed that learning drama appreciation through Stratta strategies allows drama students to be more creative and adapt to the coronavirus pandemic. A variety of drama learning activities are introduced to the students, ranging from script reading to staging and editing staging videos.